[RETRACTED] Dari Rekreasi ke Praktik Perjudian: Urgensi Pembentukan Qanun Domino di Kota Langsa, Aceh - Putri Alya Zuhra Al Faerah; Kafrawi Kafrawi; Faisal Faisal; Rasyidin Rasyidin (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
The game of dominoes (meen batee) is part of the recreational culture of the Acehnese people. However, in practice, this game has shifted into an activity associated with gambling, resulting in social, economic, and moral consequences, as well as violations of state law, customary law, and sharia law. Therefore, the Government of Langsa City needs to immediately enact a qanun specifically regulating the game of dominoes (meen batee) to ensure legal certainty and maintain public order. This study employs a normative-juridical method combined with a socio-legal approach. It examines the national and regional legal framework, including qanun and regional regulations, while integrating perspectives from social sciences, political science, and the specific characteristics of Islamic law implementation. The findings reveal that such regulation is necessary to provide legal certainty, protect the community from economic losses, and preserve cultural values and Islamic principles from distortion through gambling-related practices. Furthermore, the proposed qanun functions as both a preventive and educational instrument, addressing legal violations while fostering public legal awareness. In conclusion, the enactment of a qanun (regional regulation) governing gambling-affiliated domino games (meen batee) represents a strategic measure to strengthen regional legal order, maintain social stability, and reaffirm Langsa City's commitment to the implementation of Islamic law.